Identification of a QTL region for ashy stem blight resistance using genome-wide association and linage analysis in common bean recombinant inbred lines derived from BAT 477 and NY6020-4 - Viteri, Diego M.; Linares, Angela M.; Miranda, Zoralys; Shi, Ainong (Frontiers in Plant Science, 2022)
Ashy stem blight (ASB), caused by the fungus Macrophomina phaseolina (Tassi) Goidanich is an important disease of common bean (Phaseolus vulgaris L.). It is important to identify quantitative trait loci (QTL) for ASB resistance and introgress into susceptible cultivars in common bean. The objective of this research was to identify QTL and single nucleotide polymorphism (SNP) markers associated with ASB resistance in a recombinant inbreed lines (RIL) derived from a cross between BAT 477 and NY6020-4 in common bean. One hundred-twenty six F6:7 RIL were phenotyped for ASB in the greenhouse. Disease severity was scored with a 1-9 scale. Genotyping was performed using a whole genome resequencing with 2x common bean genome size coverage and over 6 million SNPs were obtained. After filtered, 72,017 SNPs distributed on 11 chromosomes were used to conduct genome-wide association study (GWAS) and QTL mapping. A novel QTL region of ~4.28 Mbp from 35,546,329 bp to 39,826,434 bp on chromosome Pv03 was identified for ASB resistance. The two SNPs, Chr03_39824257 and Chr03_39824268 located at 39,824,257 bp and 39,824,268 bp on Pv03, respectively were identified as strongest markers associated with ASB resistance and the gene Phvul.003G175900 (drought sensitive, WD repeat-containing protein 76) located at 39,822,021 – 39,824,655 bp on Pv03 was recognized as one candidate for ASB resistance in the RIL and the gene contained the two SNP markers. The QTL and SNP markers may be used to select plants and lines for ASB resistance through marker-assisted selection (MAS) in common bean breeding.